A microfluidic cell size/density sensor by resistive pulse detection - Kang, Yuejun (2013)
We developed a microfluidic resistive pulse-based cell sensor driven by a syringe pump and a small electric field to precisely count and size yeast and E. coli, as well as measure their density. The microfluidic sensor consisted of one small sensing aperture (10 µm×8 µm cross-section and 15 µm long) and four side channels. Two side channels were designed to apply a small voltage across the aperture, and the other two were connected to a commercial differential amplifier to detect the trans-aperture voltage modulation caused by cells. Yeast cells were delivered to the resistive pulse sensor through the syringe pump at different flow rates. The measured yeast cell density before dilution was 3.53×108 cells/mL with the average diameter of 3.30 µm (18.83 µm3 in volume) at 1 nL/s, and 3.46×108 cells/mL with the average diameter of 3.40 µm (20.49 µm3 in volume) at 10 nL/s. The same device was used to analyze a population of E. coli, yielding the average volume of 5.36 µm3 and density of 1.79×106 cells/mL. We expect this simple and versatile resistive pulse-based sensor would have potential to realize on-site and on-line cell analysis.